Factors Affecting Staff Turnover of Young Academics: Job Embeddedness and Creative Work Performance in Higher Academic Institutions - Shah, Imran Ahmed; Yadav, Amit; Afzal, Farman; Shah, Syed Maqsood Zia Ahmed; Junaid, Danish; Azam, Sami; Jonkman, Mirjam; De Boer, Friso; Ahammad, Ronju; Shanmugam, Bharanidharan (Frontiers in Psychology, 2020)
Young academics have been facing a problem of high turnover rate due to missing links between the institutions’ policies and the performance. This study explores the effect of job embeddedness and community embeddedness on creative work performance and intentions to leave of young teaching staff in academic institutions in Pakistan. In this study, 300 qualified young academics from public and private universities were selected as subjects and asked to complete a questionnaire. Data were collected via mail-survey. A variance-based structural equation model is employed to measure the path model. The results show that the fit-dimension of organizational- and community- embeddedness, along with the moderating effect of organization size and the availability of nearby alternative jobs have a significant impact on improving perceived creative performance and reducing staff turnover intentions. this study suggests that organizations should focus on organizational-fit and community-fit constructs in their nurturing strategies to embed young teachers in their academic institutions. This study also suggests that monetary rewards only are relatively ineffective to improve retention. Hence, public and private sector universities should facilitate meaningful contributions from young teachers in creative work and provide opportunities for social interactions and personal development.